2019
DOI: 10.1038/s41467-019-11528-8
|View full text |Cite
|
Sign up to set email alerts
|

Transition metal-free phosphonocarboxylation of alkenes with carbon dioxide via visible-light photoredox catalysis

Abstract: Catalytic difunctionalization of alkenes has been an ideal strategy to generate structurally complex molecules with diverse substitution patterns. Although both phosphonyl and carboxyl groups are valuable functional groups, the simultaneous incorporation of them via catalytic difunctionalization of alkenes, ideally from abundant, inexpensive and easy-to-handle raw materials, has not been realized. Herein, we report the phosphonocarboxylation of alkenes with CO 2 via visible-light photore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
62
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 183 publications
(64 citation statements)
references
References 67 publications
0
62
0
2
Order By: Relevance
“…17 Due to their innate nucleophilicity, they are excellent traps for electrophilic radicals, leading to the formation of a nucleophilic aamino radical I (Scheme 1A, a). The latter can then react with a radical trap, 18 undergo oxidation to the a-amino cation, [19][20][21] reduction to the a-amino anion, 22 or addition to an organometallic species followed by reductive elimination. 23 Despite the efficiency associated to such transformations, all enamide difunctionalizations reported so far are based on the initial addition of a highly reactive electrophilic radical, limiting functional group tolerance and the structural diversity of the obtained products.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…17 Due to their innate nucleophilicity, they are excellent traps for electrophilic radicals, leading to the formation of a nucleophilic aamino radical I (Scheme 1A, a). The latter can then react with a radical trap, 18 undergo oxidation to the a-amino cation, [19][20][21] reduction to the a-amino anion, 22 or addition to an organometallic species followed by reductive elimination. 23 Despite the efficiency associated to such transformations, all enamide difunctionalizations reported so far are based on the initial addition of a highly reactive electrophilic radical, limiting functional group tolerance and the structural diversity of the obtained products.…”
Section: Introductionmentioning
confidence: 99%
“…It is important to stress that such an approach would completely change the type of transformations accessible, as the rst step would involve reaction with a nucleophile, in opposition to the electrophilic radical already intensively investigated. [17][18][19][20][21][22][23] Although this strategy appears highly attractive to answer current limitations in enamide functionalization, only one example of ene-carbamate hydroacetoxylation has been reported by Nicewicz and co-workers. 29 When considering the importance of nitrogen-containing compounds, a difunctionalization of enamides via photocatalytic Umpolung would be highly desirable.…”
Section: Introductionmentioning
confidence: 99%
“…In 2019, Yu and co‐workers demonstrated that phosphonocarboxylation of activated alkenes 44 (e.g., styrenes, acrylates, enolsilanes, and enamides) with di(aryl‐ or alkyl)phosphine oxides 45 and phosphites, and CO 2 under metal‐free photoredox catalytic conditions (Scheme 10 a). [23] The direct quenching of excited photocatalyst by phosphine oxide in combination with base warranted the generation of phosphorous‐centered radical 47 , which engaged in the difunctionalization of styrenes, acrylates, and enamides to finally furnish β‐phosphonocarboxylic and β‐phosphonoamino acids 46 (Scheme 10 b). However, alkyl enamides and unactivated alkenes remained unreactive under these reaction conditions.…”
Section: Co2 Incorporation Into Alkene Systemsmentioning
confidence: 99%
“…For example, Iwasawa [5e,s] and König [5n] both realized regioselective hydrocarboxylations of alkenes via visible‐light photoredox and transition‐metal dual catalysis. Martin, [5h] Wu, [5r] Li [5z] and our group [5j,x,ab] have developed different visible light‐driven difunctionalizing carboxylations of alkenes. These previously reported methods, however, are limited to activated alkenes, including styrenes and acrylates.…”
Section: Introductionmentioning
confidence: 99%